Identifikasi dan Penanganan Gangguan Mesin Diesel melalui Pemeliharaan Korektif di PLTD Jayapura - Fellezia Rahel Violeta Felle (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2025)
Corrective maintenance is one of the maintenance strategies performed after system failures or malfunctions occur, particularly in diesel power plants (PLTD) that play a crucial role in supplying electricity to remote areas such as Jayapura. This study aims to identify the types of failures occurring in diesel engines at the Jayapura PLTD and to evaluate the corrective maintenance actions implemented. Data were collected through direct observation during an internship program, interviews with technicians, and analysis of historical maintenance and failure records. The results indicate that the most common failures occurred in the lubrication system, fuel system, and cooling system. Corrective actions included component repairs, spare part replacements, and system adjustments. The application of timely and appropriate corrective maintenance significantly reduced machine downtime and improved the reliability of the power generation system. This study recommends integrating corrective and preventive maintenance strategies to maximize operational efficiency of the PLTD.